Modernization and foreign trade in the health services - Leon, Francisco (ECLAC SantiagoCL, 2000)
Examines the impact of modernization of the health system on foreign trade in health services during the period 1983-1999 and looks at future prospects in this area. Establishes linkages between specific aspects of reform and modernization of the sector and imports and exports of specific services produced or required by the health system and the public.